Preventive neuromuscular training for young female athletes: comparison of coach and athlete compliance rates - Sugimoto, D.; Mattacola, C. G.; Bush, H. M.; Thomas, S. M.; Foss, K. D. B.; Myer, G. D.; Hewett, T. E. (Journal of Athletic Training, 2017)
Context: Fewer athletic injuries and lower anterior cruciate ligament injury incidence rates were noted in studies of neuromuscular-training (NMT) interventions that had high compliance rates. However, several groups have demonstrated that preventive NMT interventions were limited by low compliance rates.